Enrolment and achievement of persons with special needs in secondary schools in science subjects: Facts and patterns (2015)
There are numerous studies on the practice of education curriculum, problems and prospects of special education programmes. However, studies on enrolment and achievement pattern of persons with special. needs in science subjects are limited. This study is therefore designed to investigate enrolment and achievement of persons with special needs in science subjects in schools. This is a descriptive study involving eight secondary schools purposefully selected from three states in the South-western part of Nigeria. The schools had a range of 227 to 1543 students’ population. The schools were both general (inclusive) and special schools. All the 55 senior secondary school students from two of these schools who offered science subjects specifically participated fully in the study. Twelve special education teachers from the sampled schools also participated. Five research questions were -answered-; Data was subjected to descriptive statistical analysis: The few students who offered science subjects achieved 3bove average Many of the students offering science subjects aspire to read medicine, nursing,-building construction among:other ^lliedj courses. They hope to work in hospitals, civil service, handicraft production and food production in that order among other places. However there are controversies on the views of the students on the reasons why science subjects are not popular among students with special education needs in Nigerian schools. It is hoped that Nigeria Teacher Educators may find means of encouraging and sustaining interest of students with, special education needs in science subjects and science related disciplines in this prevailing technology-driven world.